Awareness and attitudes towards eye donation among medical and allied health students in Jeddah, Saudi Arabia - Mahmood Showail; Turki A. AlAmoudi; Esraa Basalem; Khalid Alshebl; Nawaf Meshal Almalki; Abdullah Al Matrafi; Mohammed Ashour (PeerJ, 2024)
Background Many national studies in Saudi Arabia have revealed a lack of knowledge about eye donation. The current study assessed awareness and attitudes towards eye donation among health faculty students in Jeddah, Saudi Arabia. It aims to increase their awareness as future healthcare providers are expected to raise general awareness to attain more local corneal donations. Methods A cross-sectional study including 1,060 health faculty students was conducted at King Abdulaziz University. Data were collected through an online questionnaire that covered participants’ demographics, academic year, knowledge, and attitudes regarding eye donation. Results Thirty-five percent of students had heard about eye donation, with the most common sources of information being social media (29%) and health workers (24%). Most respondents, 61% (n = 643), indicated willingness to donate their eyes after death. Of these respondents, 93% (n = 986), 6.8% (n = 72), and 0.2% (n = 2) had poor, fair, and good knowledge levels, respectively. A total of 66% (n = 696) and 34% (n = 364) had negative and positive attitudes, respectively. Conclusion Students in this study showed low levels of knowledge and negative attitudes about eye donation. Students should be adequately educated about the significance of eye donation.